Шпага першої третини ХІХ ст. російського державного діяча Олександра Дмитровича Балашова в колекції НМІУ - Попельницька, О.О. (Історія давньої зброї. Дослідження 2014, 2014)
Стаття присвячена вивченню музейного предмета з зібрання Національного музею історії України – російської офіцерської шпаги, виготовленої у першій третині ХІХ ст., власником якої був російський державний діяч О. Д. Балашов (1770–1837). У статті аналізуються топонімічні написи на клинку, що мають відношення до видатних подій у біографії О. Д. Балашова та робиться спроба ідентифікувати напис «Swalling», виконаний на обуху клинка, як тавро одного з представників шведської ковальської династії Сваллінгів. Статья посвящена изучению музейного предмета из коллекции Национального музея истории Украины – русской пехотной офицерской шпаги образца 1798 г., изготовленной в первой трети ХІХ в., владельцем которой был русский государственный деятель А. Д. Балашов (1770–1837). В статье проанализированы топонимические надписи на клинке, имеющие отношение к памятным событиям биографии А. Д. Балашова. Автором идентифицирована надпись «Swalling», выполненная по обуху клинка, как клеймо одного из представителей шведской кузнечной династии Сваллингов. Шпага А. Д. Балашова представляет интерес не только как произведение оружейного искусства, но и как историческая реликвия, отразившая события эпохи в судьбе одного человека – офицера и дипломата. Dr. Olena Popelnytska devoted her article to the the study of museum objects from the collection of the National museum of history of Ukraine. The sample in question is the Russian Pattern 1798 Infantry sword. Author analysed the toponymic inscriptions on the blade with respect to the outstanding events in the biography of Аlexander Balashov. Dr. Popelnytska identified the inscription «Svalling» engraved on the forte of the blade, connecting it with the dynasty of Svalling – the royal armourers from Sweden. The sword of Аle xander Balashov is of high interest not only as a crafted masterpiece, but also as a historical relic. Through the fate of one man, one can study the era of Alexander I, the War of the Russian Empire with Napoleonic France, where Аlexander Bala shov participated as an officer and as a diplomat.